Thermo-rheological improvement of magnetorheological foam with the addition of silica nanoparticles - Mohamed Khaidir, Rahayu Emilia; Nordin, Nur Azmah; Mazlan, Saiful Amri; Ubaidillah, Ubaidillah; Rahman, Hamimah Abd; Marzuki, Ainaa Amirah; Wahab, Siti Aisyah Abdul (Institute of Physics, 2024)
Magnetorheological (MR) foam has become a potential soft robotic gripper-based material that can provide a better grasping force and handling objects due to its ability in varying stiffness in correspond to applied magnetic fields. However, MR foams are facing degradation issue that may reduce the storage modulus when often exposed to thermal exposure from the operating system of a device. Therefore, this study focuses on improving the storage modulus and simultaneously enhancing the thermal properties of MR foam. Hence, silica nanoparticles were introduced as an additive to achieve the improvement target. MR foams were embedded with different concentrations of silica nanoparticles from 0 to 5 wt.%, and the corresponding rheological properties was examined under different temperature conditions from 25 °C to 65 °C. The results revealed that increasing temperatures have reduced the storage modulus of MR foams, however, the embedded silica has countered the drawbacks by strengthening the interfacial interactions between CIP-polyurethane foam matrix. In addition, the morphological characteristics of MR foams also showed less debris or peel-off PU foam with silica nanoparticles. Besides, the silica nanoparticles have delayed the thermal degradation of MR foam for approximately 30 °C.